PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Geby Wulandari; Desmiyawati -; Al Azhar Lukman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Capital work is the company’s investment in current assets, such as cash, inventory, and accounts receivable. Working capital needed to carry out activities of daily operational a company to abtain the expexted profit. Head of the company must the ensure that the appropriate amount of working capital that can be run with the company’s operations and efficiently. This study aimed to determine the effect of cash turnover, Inventory turnover and accounts receivable turnover against profitability. One way to increase profitability is to increase the cash turnover, inventory turnover and accounts receivable turnover.Population in this study is a mining company listed on the indonesia stock exchange in 2009-2012.based on purposive sampling method obtained 11 mining companies as sample in this study. Testing was conducted with regression method. The processing of data ussing SPSS for windows ver 17.The results of this study started that the cash flows are not significantly influence the profitability of the significant value of 0,146 (more than 5%) and the effect of -0,229. For the inventory turnover ratio has no significant effect on profitability significantly 0,512 (more than 5%) and the effect of 0.058. while the accounts receivable turnover significantly influence the profitability of the significant value of the significant value of 0,001 (less than 5%) and the effect of 0,833.Keywords: Cash Turnover, Inventory Turnover, Accounts Receivable Turnover and Profitability.